ANALISIS KINERJA PENYULUH PERTANIAN BERDASARKAN PERSEPSI KELOMPOK TANI DI KELURAHAN TARATARA SATU KECAMATAN TOMOHON BARAT KOTA TOMOHON - Sandy Alfa Stefano Sambouw; Elsje Pauline Manginsela; Jane Sulinda Tambas (Sam Ratulangi University, 2020)
This study aims to describe how the performance of agricultural instructors based on the perceptions of farmer groups in Taratara Satu Village, West Tomohon District, Tomohon City. The research was conducted from February to April 2020. The data used are primary and secondary data. Primary data were obtained through direct interviews with 18 respondents using a questionnaire and secondary data were obtained from the government office of the Taratara Satu village. The sampling method used purposive sampling method. The research results showed, 74 percent of farmers said that the extension workers had carried out their functions well, while 26 percent said that the extension workers were lacking in carrying out their roles and functions.